Recycling of E-Cadherin: A Potential Mechanism for Regulating Cadherin Dynamics - Le, Tam Luan (The Rockefeller University Press, 1999)
E-Cadherin plays critical roles in many aspects of cell adhesion, epithelial development, and the establishment and maintenance of epithelial polarity. The fate of E-cadherin once it is delivered to the basolateral cell surface, and the mechanisms which govern its participation in adherens junctions, are not well understood. Using surface biotinylation and recycling assays, we observed that some of the cell surface E-cadherin is actively internalized and is then recycled back to the plasma membrane. The pool of E-cadherin undergoing endocytosis and recycling was markedly increased in cells without stable cell-cell contacts, i.e., in preconfluent cells and after cell contacts were disrupted by depletion of extracellular Ca(2+), suggesting that endocytic trafficking of E-cadherin is regulated by cell-cell contact. The reformation of cell junctions after replacement of Ca(2+) was then found to be inhibited when recycling of endocytosed E-cadherin was disrupted by bafilomycin treatment. The endocytosis and recycling of E-cadherin and of the transferrin receptor were similarly inhibited by potassium depletion and by bafilomycin treatment, and both proteins were accumulated in intracellular compartments by an 18°C temperature block, suggesting that endocytosis may occur via a clathrin-mediated pathway. We conclude that a pool of surface E-cadherin is constantly trafficked through an endocytic, recycling pathway and that this may provide a mechanism for regulating the availability of E-cadherin for junction formation in development, tissue remodeling, and tumorigenesis.